Dermoscopic Features of Cutaneous Endometriosis Arising in a Cesarean Scar: A Case Report - Kevin Yang; Karim Saleh (Case Reports in Dermatological Medicine)
Cutaneous endometriosis is a rare manifestation of endometriosis, and few reports on its dermoscopic features have been published. In this case report, we present a 40-year-old female with cutaneous endometriosis arising in a caesarean scar, exhibiting unique and distinct dermoscopic features. The patient presented with a nodular, papillomatous growth in the right end of the scar, and dermoscopic examination revealed structureless red papillomatous projections, as well as nonpapillomatous areas with red dotted vessels surrounded by a white reticular network. A biopsy confirmed the diagnosis of endometriosis. To our knowledge, this is the first report of such dermoscopic features in cutaneous endometriosis arising in a caesarean scar. Our case report adds to the current limited knowledge of dermoscopic features of cutaneous endometriosis and may help in the diagnosis of this condition.